Feasibility Of Myritel Lettuce Business With Hydroponic System At Alfa Hydroponic MSMEs Tasikmalaya Regency: - Husna, Ibrahim; Fitriadi, Budhi Wahyu; Jakiyah, Ulpah (Utami Publisher, 2024)
Hydroponic lettuce cultivation will run well if production inputs are available and accompanied by a good management system. Business feasibility is an activity to examine a business activity as a whole with the aim of considering whether the business activity is feasible to run or not. This research was conducted at Alfa Hidroponik owned by Mr. Raihan located in Kp Leles Kidul, Ciawi Village, Ciawi District, Tasikmalaya Regency. Data collection techniques through interviews and documentation. Interviews were conducted directly with the owner of the hydroponic lettuce business. The data analysis technique used was using the quantitative descriptive analysis method, namely Business feasibility analysis with the R/C ratio. The total production cost of hydroponic alpha lettuce cultivation is IDR 29,659,500, - with a total income of IDR 48,035,000, - and a total income of IDR 18,375,500, - with an R/C ratio of 1.62, meaning that for every rupiah of costs incurred, an income of IDR 1.62 is obtained. So it can be concluded that the hydroponic alpha lettuce cultivation carried out by Mr. Raihan in Ciawi Village, Ciawi District, Tasikmalaya Regency is worthy of being developed.